2021
DOI: 10.5371/hp.2021.33.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Midterm Results of Triflange Patient Matched Implants for Extensive Acetabular Bone Defect

Abstract: Purpose Reconstruction of extensive acetabular bone defects is one of the most challenging problems encountered by arthroplasty surgeons. Triflange patient matched implants (PMI) offer the potential advantages of immediate, rigid fixation with a superior individualized fit. The purpose of this study was to evaluate the clinical and radiographic midterm results of PMI in extensive acetabular defect reconstruction. Materials and Methods The current prospectively designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…( 47 ) 2021 RCS 19 19 77 (52–91) 8/11 NA 53 (17–88) 2014 New Kawalkar et al . ( 48 ) 2021 RCS 13 13 69 (57–86) 5/8 27 (NA) 50 (18–70) 2011 New Scharff-Baauw et al . ( 49 ) 2021 PCS 49 49 68 (41–89) 8/41 27.0 (19–44) 24 (NA) 2013 New Sershon et al .…”
Section: Resultsmentioning
confidence: 99%
“…( 47 ) 2021 RCS 19 19 77 (52–91) 8/11 NA 53 (17–88) 2014 New Kawalkar et al . ( 48 ) 2021 RCS 13 13 69 (57–86) 5/8 27 (NA) 50 (18–70) 2011 New Scharff-Baauw et al . ( 49 ) 2021 PCS 49 49 68 (41–89) 8/41 27.0 (19–44) 24 (NA) 2013 New Sershon et al .…”
Section: Resultsmentioning
confidence: 99%
“…The anatomy of the pelvis had changed as a result of aseptic loosening, so the acetabular cup could not be placed in its normal position. In human medicine, if the bone stock in the acetabulum is insufficient, a patient-tailored cage is used for THR surgery ( 16 18 ). Recently in veterinary medicine, Castelli et al ( 19 ) reported a single case using a similar 3D-printed patient-specific acetabular implant in large-breed dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Often, the explantation of loose implants may be necessary as a last treatment option. Recently, as a way of overcoming these structural limitations, three-dimensional (3D)-printed patient-specific implants for the revision of THR with insufficient acetabular bone stock have been reported in humans ( 16 18 ) and large-breed dogs ( 19 ). However, revision strategies for mTHR in small-breed dogs have not yet been reported clinically.…”
Section: Introductionmentioning
confidence: 99%